Integrating Islamic Values and Individual Characteristics to Overcome Learning Difficulties in Islamic boarding schools - Teti Ratnawulan; Ashri Hidayati; Baden Badrudin; Aznan Che Ahmad; Rifqi Zaeni Achmad Syam; Willya Achmad (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
Learning difficulties in Islamic boarding schools remain a complex and persistent issue, particularly due to the integration of religious and general education systems, which create cognitive, emotional, and social challenges for students as they adapt to intensive learning environments. This study aims to examine the types of learning difficulties students experience, analyze the implementation of Islamic approaches to address these challenges, and evaluate the relationship between individual characteristics and the effectiveness of these interventions within the boarding school context. The research employed a qualitative case study design at Islamic Boarding School Syamsul’ulum, Sukabumi, Indonesia, using in-depth interviews, participant observation, and document analysis, with data analyzed through thematic analysis and triangulation to ensure credibility and contextual validity. The findings reveal that learning difficulties are multidimensional, including cognitive barriers in understanding classical Islamic texts, weak memorization and retention, low intrinsic motivation, and emotional instability such as homesickness, while Islamic approaches such as moral guidance (mau’izhah hasanah), spiritual reinforcement, Qur’an-based contextual teaching, and ukhuwah culture function as structured psycho-spiritual interventions that enhance emotional regulation, resilience, and learning engagement. These findings imply that educational institutions, particularly Islamic boarding schools, should adopt an integrative educational model that aligns spiritual practices with students’ individual characteristics and adaptive instructional strategies to effectively address learning difficulties and improve both academic and character development outcomes.